Dilated Cardiomyopathy, Cholangiohepatitis and Hepatic Necrosis in Captive Lagothrix Lagotricha (Family Atelidae, Non-Human Primate) (Revista Sistemas de Producción Agroecológicos, 2026)
Colombia harbors more than 30 primate species, many threatened or endangered, positioningbioparks as critical actors in species conservation and public environmental education. We report a fatal case in an adult male woolly (churuco) monkey (Lagothrix lagotricha) maintained atLos Ocarros Biopark (Meta, Colombia) that progressed to multiorgan failure. On July 28, 2023,the animal presented inappetence, weakness, and aversion to the handling area. Empiricaltherapy was initiated with oxytetracycline (20 mg/kg IM q48h) and vitamin B complex (10 µg/kg IM, single dose). Hematology revealed leukocytosis; serum biochemistry showed elevatedALT and increased BUN/urea, suggestive of azotemia. On August 4, the patient was referredto the University of Los Llanos Veterinary Clinical Center. Under ketamine anesthesia (5 mg/kgIM), echocardiography, thoracic radiography, hematology, and biochemistry were performed,demonstrating cardiomegaly, mild hydropericardium, ventricular hypertrophy, right-sidedheart failure with ascites, hepatic congestion, and renal disease compatible with glomerulitis.Physical examination identified a grade 3/6 systolic murmur, and coproparasitology detectedStrongylus spp. Management included furosemide (2 mg/kg PO q12h × 5 days), diltiazem (2mg/kg PO q24h × 5 days), pyrantel pamoate (11 mg/kg PO), and adjunct homeopathic preparations (Trinov, Coenzyme, Ubichinon; 0.3 mL each PO BID). A transient improvement in appetiteand behavior was noted on August 8. During physical restraint for follow-up on September 6,the animal developed shock and died suddenly. Necropsy (September 13) documented a markedly enlarged heart (~60% of thoracic volume) with serosanguineous pericardial effusionmild tricuspid valve deformity, severe coronary congestion, irregular kidneys with poor corticomedullary distinction and partially adherent capsule, and adrenal hemorrhages. Death wasattributed to multiorgan failure secondary to right congestive heart failure and chronic renaldisease. This case underscores the need for early detection, continuous monitoring, and specialized veterinary care for captive neotropical primates.